IMPLEMENTATION OF ISLAMIC SPIRITUAL PROGRAMS IN THE FORMATION OF MORALS AND RELIGIOUS AWARENESS OF STUDENTS OF SMA NEGERI 1 STABAT LANGKAT REGENCY - Latifah, Siti; Abrianto, Danny; Imran, Zulfi (Proceeding International Seminar of Islamic Studies, 2023)
The ROHIS (Islamic Spirituality) program in the formation of morals and religious awareness in students at SMA Negeri 1 Stabat is important to implement. Increasing the current of globalization that takes away the interest and awareness of teenagers from the importance of religion, programs like this deserve to be implemented. However, in order for this program to run well, there are 2 main things, namely, preparing worship facilities and carrying out religious activities. This study aims to find out how the implementation of the ROHIS (Rohani Islam) program in the formation of morals and religious awareness. Furthermore, to find out how the obstacles that occur in the implementation process of forming students' morals and religious awareness through the ROHIS (Islamic Spiritual) program. In addition, it is also to find out how solutions in overcoming obstacles in the implementation process of forming students' morals and religious awareness through the ROHIS (Islamic Spiritual) program. In this study researchers used descriptive qualitative methods and types of pedagogic approaches, psychological approaches and religious approaches. Data obtained through informants are processed with data collection techniques. The field data collection technique consists of three parts, namely observation, interview, and documentation.